STATUS OF MANGROVES IN MAURITIUS - Chandani Appadoo (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Mangroves play an important role in the coastal ecosystem of Mauritius. Two species of mangroves, Bruguiera gymnorrhiza (L.) Lam., and Rhizophora mucronata Lam., have been identified so far. The latter species is more dominant and occurs in pure stands in most of the swamps. Loss of biodiversity due to the destruction of wetlands, mangroves and corals is one of the priority issues identified in the National Environment Strategies. Mangrove and Coral reef management and protection is one of the key strategies in addressing coastal zone challenges in Mauritius. Very few scientific studies exist on mangroves in Mauritius. Currently there are no scientific studies on the fauna and flora inhabiting mangrove ecosystems. This is an area that requires further research. Therefore a lot of work remains to be done with regards to the mangroves. Moreover, future management programs will need to look into the factors threatening mangrove ecosystems.